Semantic plurality English collective nouns and other ways of denoting pluralities of entities - Gardelle, Laure (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2019)
"This monograph proposes a comparative approach to all the ways of denoting 'more than one' entity, from collective and aggregate nouns (with the first-ever typology), to count plurals, partly substantivised adjectives and conjoined NPs. This semantic feature approach to plurality, which cuts across number, the count/non-count distinction, and lexical/NP levels, reveals a very consistent Scale of Unit Integration, which establishes clear-cut boundaries for collective nouns, and accommodates cases such as three elephant, cattle or a chain of islands. The study also offers a refined understanding of aggregate nouns (a category nearly as large as that of collective nouns) and quantification in pseudo-partitives, develops Guillaume's notion of 'internal plurality', and proposes the innovative concept of 'hyperonyms of plural classes' (e.g. furniture). The Animacy Hierarchy is also found to be influential, beyond hybrid agreement. The book is meant to be accessible to scholars of any theoretical background interested in these topics"--